Tathwīr Mawād Ta’līm Al-Lugoh Al-Arabiyyah li Qowā’id ‘ala asās Kharāith Mafāhīm - Rohmatun Nurul Hidayah; Nurul Hidayah; Hana Chebaik (University of Darussalam Gontor, 2022)
This research is motivated by students' difficulties in understanding Arabic, especially in qawa'id material. This is due to the lack of qawa'id material contained in the teaching materials provided by the school. The amount of interest in learning Arabic and the presentation of the book presented is too monotonous. Based on this, interesting Arabic teaching materials should be developed and contain qawa'id materials to facilitate students' understanding. Therefore, the development of qawa'id teaching materials based on mind mapping is urgently needed.The problems studied in this study are (1) what is the process for developing mind mapping-based Arabic qawa'id teaching materials? (2) how is the feasibility of mind mapping-based Arabic qawa'id teaching materials? This study was designed using research and development (R&D) methods. The steps taken in this study only reached the trial stage (small group). Research data obtained through test techniques, interviews, observation, questionnaires and documentation.The results of this study are the expert test assessment, namely validation to material experts who reach 86.67% are in very valid qualifications, teaching material design experts reach 80% are in valid qualifications and learning experts who reach 90% are in very valid qualifications. After that, conducting trials in small groups, namely by 6 students with obtaining an average percentage of 93% which shows that mind mapping-based qawa'id teaching materials are feasible to use and have shown real effectiveness as evidenced by the results of the t-test on calculations manuals.